Soil-plant-herbivore interactions and nutrient dynamics in semi-arid grazing systems in northeastern Brazil and western USA - Menezes, Rômulo Simões Cezar, author; Elliott, Edward T., advisor; Peterson, Gary A., advisor; Coughenour, Michael B., committee member; Paustian, Keith, committee member (Colorado State University. Libraries, 1999)
Nutrient cycling, availability, and use efficiency are key issues of sustainability and control important aspects of ecosystem function. In the series of studies in this dissertation, we evaluate how human-induced disturbances and interactions between soil, plants, and herbivores influence nutrient cycling, productivity, and ecosystem structure in semi-arid grazing systems in northeastern Brazil and Colorado, USA. We found that the presence of tree species within pastures of C. ciliaris in northeastern Brazil led to increases in soil nutrient levels, cycling rates, and availability in comparison to areas where all trees were removed. In Rocky Mountain National Park (RMNP), Colorado, we found that herbivores had a significant influence on nutrient pools, fluxes between pools, and also on ecosystem structure by possibly reducing the ability of Salix shrubs to take up N from the groundwater, which may affect the regeneration of Salix communities in that site. Overall, our findings indicate that the presence and preservation of trees or shrubs in the semi-arid grazing systems in northeastern Brazil and RMNP contributed to the maintenance of ecosystem function by increasing the capture, retention, and availability of nutrients and plant productivity in comparison to disturbed systems where the density of trees or shrubs was reduced.
Keywords: ecology; soil sciences; zoology